Description Of Keyword Analysis: A Bibliometric Study Of Interpersonal Communication - Darmawati Darmawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The aim of this study was to assess the most relevant themes related to interpersonal communication by bibliometric analysis using the keyword